Modeling of thermal regime of manufacturing premises using graph theory - Fialko, N. M.; Zhelyh, V. M.; Dzeryn, O. I. (Видавництво Львівської політехніки, 2013)
The data on the application of graph theory to model the thermal state of the working area of industrial facilities on the example of agricultural building department piglets and sows. Наведено дані щодо застосування теорії графів для моделювання теплового стану робочої зони виробничих приміщень на прикладі сільськогосподарської будівлі цеху поросят і свиноматки.
Keywords: graph theory; department of piglets and sows; thermal state; теорія графів; цех поросят і свиноматок; тепловий стан